Genetic diversity of mindi (Melia azedarach) from community forest in Deli Serdang, North Sumatra, Indonesia revealed by microsatellite marker - RIDAHATI RAMBEY; ARIDA SUSILOWATI; NELLY ANNA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Rambey R, Susilowati A, Anna N. 2019. Genetic diversity of mindi (Melia azedarach) from community forest in Deli Serdang, North Sumatra, Indonesia revealed by microsatellite marker. Biodiversitas 20: 1708-1712. Melia azedarach or locally known as mindi is fast growing and one of important tree species for community forests especially in West Java and North Sumatra, Indonesia. High demand for its wood must be accompanied by increased productivity through planting of high-quality seed. There is still lack of information about genetic diversity of mindi from different seed source in North Sumatra. Therefore, our research was conducted to determine genetic diversity of mindi from different seed source in North Sumatra through microsatellites marker. Leaf samples originated from three populations Percut Sei Tuan, Pancur Batu and Biru-Biru were used in this study. The SSR markers were from Azadirachta indica i.e. Ai5, Ai 11, Ai 13, Ai 14 and Ai 34. Molecular data were analyzed using Popgene and NTsys version 2.0. The result showed that number of alleles (na) ranging from 1.80 to 2.80, and percentage of polymorphic loci (PPL) ranging from 60 to 80 %. The level of genetic diversity showed that mindi in North Sumatra has moderate value (He: 0.244 to 0.269). It indicated that assessment of genetic diversity of M. azedarach North Sumatra is necessary for improvement and conservation of a species.